A robotic system for real-time analysis of inhaled submicron and microparticles - Alexander J. Kaiser; Cassie Salem; Bob J. Alvarenga; Anthony Pagliaro; Kelly P. Smith; Luis G. Valerio, Jr.; Kambez H. Benam (iScience, 2021)
Summary: Vitamin E acetate (VEA) has been strongly linked to outbreak of electronic cigarette (EC) or vaping product use-associated lung injury. How VEA leads to such an unexpected morbidity and mortality is currently unknown. To understand whether VEA impacts the disposition profile of inhaled particles, we created a biologically inspired robotic system that quantitatively analyzes submicron and microparticles generated from ECs in real-time while mimicking clinically relevant breathing and vaping topography exactly as happens in humans. We observed addition of even small quantities of VEA was sufficient to alter size distribution and significantly enhance total particles inhaled from ECs. Moreover, we demonstrated utility of our biomimetic robot for studying influence of nicotine and breathing profiles from obstructive and restrictive lung disorders. We anticipate our system will serve as a novel preclinical scientific research, decision-support tool when insight into toxicological impact of modifications in electronic nicotine delivery systems is desired.